An improved DNA isolation technique for PCR detection of Strongyloides stercoralis in stool samples - Repetto, Silvia (2013)
Strongyloides stercoralis is a nematode that causes severe infections in immunocompromised patients. The low parasitic burden of chronically infected patients makes diagnosis difficult to achieve by conventional methods. Here, an in-house (IH) method for the isolation of parasite DNA from stools and a PCR assay for the molecular diagnosis of S. stercoralis were optimized. DNA yield and purity improved with the IH method which included a step of incubation of stool samples with a glycine–SDS buffer and mechanical disruption prior to DNA extraction. For the PCR assay, the addition of bovine serum albumin was required to neutralize inhibitors present in stool. The analytical sensitivity of the PCR using DNA as template, isolated with the IH method, was superior to the commercial one. This study demonstrates that a combined method that adds the step of glycine–SDS buffer incubation plus mechanical disruption prior to DNA isolation with the commercial kit increased PCR sensitivity to levels of the IH method. Finally, our assay was tested on 17 clinical samples. With the IH method for DNA isolation, a S. stercoralis specific band was detected by PCR in the first stool sample in all patients (17/17), while with the commercial kit, our S. stercoralis-specific band was only observed in 7 samples. The superior efficiency of the IH and combined methods over the commercial kit was demonstrated when applied to clinical samples with low parasitic burden. These results show that the DNA extraction procedure is a key to increase sensitivity of the S. stercoralis PCR assay in stool samples. The method developed here could help to improve the molecular diagnosis of S. stercoralis.